Pengaruh Komitmen dan Motivasi Kerja terhadap Organizational Citizenship Behavior pada Karyawan PT. Vadhana Internasional Duri - Simamora, Juan Felix Fransiskus; Syahreza, Dina Sarah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the influence of commitment and motivation on of PT. Vadhana Internasional Duri employees. This research uses quantitative methods with a sampling technique using Total Sampling. The population in this study was all 73 employees of the PT. Vadhana Internasional Office. The data collection techniques used were observation and questionnaires. The data analysis technique used is the Multiple Linear Regression Model and Hypothesis testing using the T Test and F Test and Coefficient of Determination, where previously the data had been tested using the Validity Test and Reliability Test. The research results show that Commitment and Motivation have a significant effect on the OCB behavior of PT. Vadhana Internasional employees. Simultaneously, Commitment and Motivation have a significant effect on OCB behavior. The adjusted coefficient of determination (adjusted R2) is 0.0442, which means that the Commitment and Motivation variables contribute to the influence of OCB behavior by 44.2% while the remaining 55.8% is determined by other variables outside this research. This shows that there are still other variables that can explain OCB behavior